Double-Diaspora in the Literature and Film of Arab Jews - Schwartz, Stephanie (Université d'Ottawa / University of Ottawa, 2012)
Inspired by the contrapuntal and relational critiques of Edward Said and Ella Shohat, this thesis conducts a comparative analysis of the literature and film of Arab Jews in order to deconstruct discourses on Jewish identity that privilege the dichotomies of Israel-diaspora and Arab-Jew. Sami Michael’s novel Refuge, Naim Kattan’s memoir Farewell, Babylon, Karin Albou’s film Little Jerusalem and b.h. Yael’s video documentary Fresh Blood: a Consideration of Belonging reveal the complexities and interconnections of Sephardic, Mizrahi and Arab Jewish experiences across multiple geographies that are often silenced under dominant Eurocentric, Ashkenazi or Zionist interpretations of Jewish history. Drawing from these texts, Jewish identity is explored through four philosophical themes: Jewish beginnings vs. origins, boundaries between Arab and Jew, the construction of Jewish identities in place and space, and, the concept of diaspora and the importance Jewish difference. As a double-diaspora, with the two poles of their identities seen as enemies in the ongoing conflict between Israel-Palestine, Arab Jews challenge the conception of a single Jewish nation, ethnicity, identity or culture. Jewishness can better be understood as a rhizome, a system without a centre and made of heterogeneous component, that is able to create, recreate and move through multiple territories, rather than ever settling in, or being confined to a single form that seeks to dominate over others. This dissertation contributes a unique theoretical reading of Jewish cultures in the plural, and includes an examination of lesser known Arab Jewish writing and experimental documentary in Canada in relation to Iraq, France and Israel.
Keywords: Jewish; diaspora; Naim Kattan; Zionism; b.h. Yael; Karin Albou; Sami Michael; Arab Jew; Mizrahi